Ewald: an extended wide‐angle Laue diffractometer for the second target station of the Spallation Neutron Source. Issue 4 (26th July 2017) - Coates, Leighton; Robertson, Lee
Abstract : The design of a macromolecular neutron diffractometer for the second target station of the Spallation Neutron Source is detailed. Abstract : Visualizing hydrogen atoms in biological materials is one of the biggest remaining challenges in biophysical analysis. While X‐ray techniques have unrivaled capacity for high‐throughput structure determination, neutron diffraction is uniquely sensitive to hydrogen atom positions in crystals of biological materials and can provide a more complete picture of the atomic and electronic structures of biological macromolecules. This information can be essential in providing predictive understanding and engineering control of key biological processes, for example, in catalysis, ligand binding and light harvesting, and to guide bioengineering of enzymes and drug design. One very common and large capability gap for all neutron atomic resolution single‐crystal diffractometers is the weak flux of available neutron beams, which results in limited signal‐to‐noise ratios giving a requirement for sample volumes of at least 0.1 mm 3 . The ability to operate on crystals an order of magnitude smaller (0.01 mm 3 ) will open up new and more complex systems to studies with neutrons which will help in our understanding of enzyme mechanisms and enable us to improve drugs against multi resistant bacteria. With this is mind, an extended wide‐angle Laue diffractometer, `Ewald', has been designed, which can collect data using crystal volumes below 0.01 mm 3 .